Fetal Anasarca in Himalayan Sheepdog - Mahajan, Mohit; Prasad, Shiv; Singh, Vipin; Arya , Damini (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Fetal anasarca (dropsy of fetus) is a congenital anomaly, grossly characterized by an increase in the fetal volume  due to excessive fluid build-up under the cutaneous layer  (subcutaneous tissue). Particularly the head and hind limbs are  involved, with concurrent accumulation within the peritoneal  and pleural cavities (Noakes et al.;, 2001). “Congenital edema,”  “hydrops fetalis” or “walrus syndrome” are other terms used  for fetal anasarca. These pups anatomically resemble hippos  and walrus and thus are called water puppies and walrus  puppies. As they are more prominent compared to normal  pups, they often result in dystocia due to fetal oversize and  lead to high infant mortality (Hopper et al., 2004; Monteagudo  et al., 2002). Pups affected with fetal anasarca may be one or  the complete litter. Anasarca is common in large and small  ruminants, but rare cases in small pet animals such as canines  and felines (Prabaharan et al., 2016) are reported. Canine  breeds predisposition to fetal anasarca is reported in English  bulldog, French bulldog, and Pugs. Studies have suggested  the use of diuretics such as thiazide as the primary treatment  for congenital edema like anasarca in the fetus (Hopper et al.,  2004; Hoskins, 2008) with only limited success.
Keywords: Fetal Anasarca; puppies; Congenital edema; hydrops fetalis